PENGARUH PROFITABILITAS, LEVERAGE, GROWTH, DAN FREE CASH FLOW TERHADAP DIVIDEND PAYOUT RATIO PERUSAHAAN DENGAN MEMPERTIMBANGKAN CORPORATE GOVERNANCE SEBAGAI VARIABEL INTERVENING - Muhammad Akhyar Adnan, Barbara Gunawan Ratri Candrasari (jaai, 2016)
This study is aimed at analyzing the influence of Profitability, Leverage, Growth, and, Free Cash Flow to the Company's Dividend Payout Ratio, by considering the Corporate Governance as an intervening variable. Subjects in this study were the companies ranked in the Corporate Governance Perception Index ranking (CGPI) conducted by the Indonesian Institute for Corporate Governance (IICG) in 2006- 2011 which published their financial statements as of December 31. The samples were 81 companies selected using purposive sampling method. The analysis tools are simple regression and path analysis.The research found that only three hypotheses are accepted, while others are rejected. The research concludes that profitability has no positive influence on dividend payout ratio; leverage negatively affect the dividend payout ratio; growth negatively affect the dividend payout ratio; free cash flow positively effect on dividend payout ratio, no positive effect of profitability on the Corporate Governance, leverage positively influencesthe corporate governance; growth has no positive influence on corporate governance; free cash flow does not influence the Corporate Governance, Corporate Governance does not affect the dividend payout ratio, and the Corporate Governance is accepted to be added in the model as an intervening variable. Keywords: dividend payout ratio (DPR), profitability (ROA), leverage (DER), growth (GROWTH), free cash flow (FCF), Corporate Governance (CG)